Acoustic Interactions with Submerged Elastic Structures - Part Ii : Propagation, Ocean Acoustics and Scattering. - Engelbrecht, Juri (Series on stability, vibration, and control of systems., 2001)
The interaction of acoustic fields with submerged elastic structures, both by propagation and scattering, is being investigated at various institutions and laboratories world-wide with ever-increasing sophistication of experiments and analysis. This book offers a collection of contributions from these research centers that represent the present state-of-the-art in the study of acoustic elastic interaction, being on the cutting edge of these investigations. This includes the description of acoustic scattering from submerged elastic objects and shells by the Resonance Scattering Theory of Flax,